Hubungan Usia, Pemakaian APD, dan Personal Higiene dengan Fungsi Kognitif pada Petani di Kabupaten Deli Serdang - Yutia Hafwenny; Nurmaini Nurmaini; Irnawati Marsaulina (Berita Kedokteran Masyarakat (BKM), 2020)
Background: Horticultural farming is a source of income for the Beringin District, Deli Serdang Regency community. Increasing agricultural yields requires the completeness of agricultural facilities, including pesticides. A preliminary survey was conducted through interviews obtained from the ten farmers interviewed. Four of them experienced signs of impaired cognitive function, such as difficulty concentrating and easy to forget. Purpose: This study aims to analyze the relationship of age, use of PPE, and personal hygiene with the cognitive function of farmers in Deli Serdang Regency.Method: This study was an observational study with a cross-sectional design. The number of samples in this study was 83 people. Data collection through interviews and observations. Methods of data analysis using the Chi-Square test with a significance level of 0.05. Results: Of 83 farmers, 36 of them experienced a disorder of cognitive function. Statistical analysis showed a relationship between age, use of PPE, and personal hygiene with cognitive function in farmers with a value (p <0.05). Conclusion: Age, PPE usage, and personal hygiene are risk factors for cognitive impairment in farmers in Beringin District, Deli Serdang Regency.